Opini Publik, Agenda Setting, dan Kebijakan Publik - Puji Rianto (Program Studi Ilmu Komunikasi, 2010)
This article is based on the theory that public opinion has important role in the democratic system. In this system, government should be responsive to public opinion that has rised in society, in which that is the only way for government to be sustained. Hence, informing public opinion, media have big influence to affect people's perception through the agenda setting. By shaping the agenda setting, the issue that is considered important by the media will be treated the same by public. Sharp reportage to the issue will influence public opinion, then, affect the government policy. Bibit-Chandra vs Polri issue proves this theory. Eventually, covering the case will not only influence government policy but also people assessment to government.